Knowledge, attitudes, beliefs and current practices regarding electronic cigarettes among smoking - Koprivnikar, Helena; Farkaš Lainščak, Jerneja (Anali PAZU, 2022)
Smoking cessation counsellors and healthcare professionals are an important source of information on the health effects of smoking and help in smoking cessation. Electronic cigarettes are a newer product, the effects of their long-term use on health are not yet known. Currently research does not confirm that they are effective in smoking cessation. The aim of this paper is to review the existing literature on knowledge, attitudes, beliefs and practices regarding electronic cigarettes among smoking cessation counsellors and healthcare professionals. Results show, that knowledge about electronic cigarettes is insufficient, and attitudes and beliefs about them are diverse and often inconsistent with existing evidence. Despite a lack of evidence, a substantial proportion of healthcare professionals recommend them for smoking cessation. It is crucial to provide uniform and evidence-based information and counselling to patients about electronic cigarettes.